2022
DOI: 10.1002/admi.202200643
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of MoS2 Decorated TiO2 Nanotubes for Photoelectrochemical Water Splitting

Abstract: MoS 2 /CdS, [15] have demonstrated a high PEC performance. It was proven that the formation of such heterostructures is beneficial for the separation of photo-generated excitons (hole-electron pairs). [13,14,16,17] In particular, MoS 2 /TiO 2 heterostructures have attracted significant interest, as MoS 2 can be used as a photosensitizer for chemically stable but wide-bandgap TiO 2 semiconductor. [18] The respective bandgap edge positions of the two semiconductors form a charge-transfer cascade, which significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
9
1
Order By: Relevance
“…The maximum photocurrent density was obtained as 135.7 μA cm −2 at 0.8 V versus Ag/AgCl for MoS 2 decorated TiO 2 /Ti foil which was two times larger than TiO 2 /Ti foil (450 °C) and TiO 2 /Ti foil (700 °C) for which photocurrent density was obtained to be ∼70 μA cm −2 and ∼67.1 μA cm −2 , respectively. The obtained photocurrent density value of MoS 2 /TiO 2 photoelectrode in this study is several times higher than the previous report photocurrent density (30 μA cm −2 ) by Shen et al (2022) [24]. The enhanced photocatalytic activity of CVD-grown MoS 2 /TiO 2 heterostructure in comparison to Shen et al (2022) study could be explained due to the few (2 or 3) layers growth of MoS 2 as confirmed by Raman spectrum (figure 4(c)).…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…The maximum photocurrent density was obtained as 135.7 μA cm −2 at 0.8 V versus Ag/AgCl for MoS 2 decorated TiO 2 /Ti foil which was two times larger than TiO 2 /Ti foil (450 °C) and TiO 2 /Ti foil (700 °C) for which photocurrent density was obtained to be ∼70 μA cm −2 and ∼67.1 μA cm −2 , respectively. The obtained photocurrent density value of MoS 2 /TiO 2 photoelectrode in this study is several times higher than the previous report photocurrent density (30 μA cm −2 ) by Shen et al (2022) [24]. The enhanced photocatalytic activity of CVD-grown MoS 2 /TiO 2 heterostructure in comparison to Shen et al (2022) study could be explained due to the few (2 or 3) layers growth of MoS 2 as confirmed by Raman spectrum (figure 4(c)).…”
Section: Resultscontrasting
confidence: 76%
“…In context to TiO 2 , which absorbs only UV light, coupling with MoS 2 offers to absorb a much wider range of sunlight. Thus, the photosensitization and band structure of MoS 2 create a suitable approach for enhancement in PEC performance [24]. It is also reported that the performance of TiO 2 -based heterostructure mostly depends on the surface morphology of the film, and the thickness of the film [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] A second doublet at 233.5 and 236.6 eV can be assigned to the Mo 6þ of MoO 3 due to the oxidation at the near surface as the sample exposed to air before the measurement. [24] At the low BE side (Figure 4a), two S 2s peaks are fitted, where one belongs to basal S 2À of MoS 2 and the other belongs to unreacted elemental S 0 or amorphous MoS 3 (S 2 2À ), which is further confirmed from the S 2p spectrum (Figure 4g). [25,26] The lower BE doublet located at 162.7 and 163.9 eV is attributed to MoS 2 , while another doublet located at 164.0 and 165.2 eV is attributed to unreacted elemental S or amorphous MoS 3 , indicating a significant amount of S 0 or S 2 2À species in the as-grown MBE-MoS 2 layer.…”
Section: Resultsmentioning
confidence: 58%
“…[ 23 ] A second doublet at 233.5 and 236.6 eV can be assigned to the Mo 6+ of MoO 3 due to the oxidation at the near surface as the sample exposed to air before the measurement. [ 24 ] At the low BE side (Figure 4a), two S 2s peaks are fitted, where one belongs to basal S 2− of MoS 2 and the other belongs to unreacted elemental S 0 or amorphous MoS 3 (S 2 2− ), which is further confirmed from the S 2p spectrum (Figure 4g). [ 25,26 ]…”
Section: Resultsmentioning
confidence: 72%